KETERSEDIAAN PANGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KETERSEDIAAN PANGAN RUMAH TANGGA PETANI PADI ANGGOTA LUMBUNG PANGAN DI KECAMATAN AMBARAWA KABUPATEN PRINGSEWU - Mariyani, Siti; Prasmatiwi, Fembriarti Erry; Adawiyah, Rabiatul (Jurnal Ilmu-Ilmu Agribisnis, 2017)
This study aims to determine household food availability of rice barn members and factors affecting the food availability. The research location is selected purposively Ambarawa of Pringsewu District with the consideration that there are most food barns in the district. Respondents were selected by using multistage sampling, which consists of 12 barns and 36 farmer members. Data analysis method used is descriptive analysis using the formula available, namely output minus input. The results showed that the availability of staple food or paddy of farmer members is included in a high category, which amounted to 1,631.94 kcal/cap/day and accounted for 67.99 percent energy availability of energy supply based on the results Widya Karya National Food and Nutrition (WNPG) X. Factors that affect the food availability of members are land size and farmers’ age (possitively), household income and education level (negatively).Key words: availability of staple food, food barns, rice farmer household member barns